2020
DOI: 10.1021/jacs.0c06066
|View full text |Cite
|
Sign up to set email alerts
|

Dismantling and Rebuilding the Trisulfide Cofactor Demonstrates Its Essential Role in Human Sulfide Quinone Oxidoreductase

Abstract: Sulfide quinone oxidoreductase (SQR) catalyzes the first step in sulfide clearance, coupling H2S oxidation to coenzyme Q reduction. Recent structures of human SQR revealed a sulfur atom bridging the SQR active site cysteines in a trisulfide configuration. Here, we assessed the importance of this cofactor using kinetic, crystallographic and computational modeling approaches. Cyanolysis of SQR proceeds via formation of an intense charge transfer complex that subsequently decays to eliminate thiocyanate. Cyanolys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…These estimations are based on considerations for LMW species; as usually with enzymes, specific protein effects could lead to further acceleration factors. In fact, recent computational estimations suggest a rate increase of ~10 5 -fold for the first step if the active site of SQOR is in the trisulfide instead of the disulfide state (73).…”
Section: Biological Implicationsmentioning
confidence: 99%
“…These estimations are based on considerations for LMW species; as usually with enzymes, specific protein effects could lead to further acceleration factors. In fact, recent computational estimations suggest a rate increase of ~10 5 -fold for the first step if the active site of SQOR is in the trisulfide instead of the disulfide state (73).…”
Section: Biological Implicationsmentioning
confidence: 99%
“…Recently, trisulfide intermediate formation has been observed during the catalytic turnover of SQR, a sufide‐catabolizing enzyme which can use cyanide as cosubstrate. Particularly, it has been shown that this enzyme harbors in its active site a cysteine trisulfide and, according to the model proposed by the authors, cyanide interacts with the catalytic trisulfide and removes one sulfur atom by a cyanolysis reaction [ 289 ].…”
Section: Multiple Interactions Exist Between Various Gasotransmittersmentioning
confidence: 99%
“…The bridging sulfur in the human SQOR cysteine trisulfide is sensitive to cyanolysis, which was initially used to detect its presence biochemically [73] . Cyanolysis was shown to occur through nucleophilic addition of the cyanide to the trisulfide, forming a transient CT complex [89] . Subsequent decay of the CT complex leads to a disulfanyl‐methanimido thioate intermediate, which was trapped in crystallo .…”
Section: Enzymology Of Human Sqormentioning
confidence: 99%
“…Subsequent decay of the CT complex leads to a disulfanyl‐methanimido thioate intermediate, which was trapped in crystallo . The bridging sulfur is extracted from this intermediate in the presence of excess cyanide, preserving the oxidation state of the active site cysteines as a cyclized 201 Cys‐S‐N‐CHS‐ 379 Cys species in an inactive form of the enzyme [89] . Incubation of cyanide‐treated SQOR with sulfide reforms the resting trisulfide, reactivating the enzyme.…”
Section: Enzymology Of Human Sqormentioning
confidence: 99%
See 1 more Smart Citation